Pelatihan Pengembangan Paket Wisata Outbond sebagai Upaya Diversifikasi Produk Pariwisata di Desa Pogalan, Kabupaten Magelang - Eki Melina Widanti; Atika Nur Hidayah; Dwi Pebrianti (JURPIKAT, 2026)
The urgency of this community service is to help Pogalan Village, Pakis District, Magelang Regency, optimize its existing tourism packages through outbound activities. Pogalan Tourism Village, as a tourist destination, boasts several attractions and attractions that have been developing since 2015, including Top Selfie Kragilan and Wisata Grenden. As a destination renowned for its natural beauty, Pogalan Tourism Village has the potential to develop outbound tourism, but its managers lack competency in this area. Therefore, training is needed to further optimize its tourism packages. The methods used in this activity include preparation, implementation, and evaluation through pre- and post-tests. The results of community service in Pogalan Tourism Village indicate that the village possesses various potentials that can be developed into outbound tourism packages. Furthermore, community knowledge regarding outbound tourism package development significantly increased after the training. Keywords: village potential, tourism package development, tourism village